Genetic Improvement of Local Chickens by Crossing with the Label Rouge (T55XSA51): Growth Performances and Heterosis Effects - Youssao, I.A.K.; Senou, M.; Dahouda, M.; Kpodekon, M.T.; Djenontin, J.; Idrissou, N-D.; Bonou, G.A.; Tougan, U.P.; Ahounou, S.; Assogba, H.M.; Bankole, E.; Rognon, X.; et al. (International Journal of Poultry Science, 2009)
The study of Genetic improvement of local chickens by crossing with the Label Rouge was carried out on the Experimentation Farm of the Polytechnic School of Abomey-Calavi, from August 2007 to may 2008. At the hatching, 6 lots of chicks were made up: the lot MnFl, composed of 47 chicks resulting from the crossing between females Label Rouge and males of North ecotype; the lot MlFn, composed of 58 chicks resulting from the crossing between North females and males Label Rouge; the lot MsFl, composed of 36 chicks resulting from the crossing between Label Rouge females and males of the South ecotype; the lot of north local chickens composed of 112 chicks; the lot of South local chickens composed of 128 chicks and the lot of Label Rouge composed of 204 chicks. Label Rouge have an age-type weight significantly higher than the cross ones (p<0.05) and those have also an age-type weight more significant than the local chickens (p<0.01). The Label Rouge had more important feed intake than the local chickens and the crossbreeds had a feed intake intermediate between the ones of the Label Rouge and the local chickens. Among the chickens resulting from a parent of North ecotype, the hens resulting from a cock of North ecotype had a weak feed efficiency compared to the one resulting from females of North ecotype. The weight average heterosis was 21.95, 14.47 and 27.69%, respectively for the cross MnFl, MlFn and MsFl. Those of the female were 1.17; 23.2 and 4.62%, respectively for the cross MnFl, MlFn and MsFl. A negative heterosis effect was obtained for the feed intake and the feed efficiency of the various crossbreeds.